Surgical Management of Popliteal Artery Aneurysms via Posterior Approach: Our Institutional Experience - Üstünışık, Çiğdem Tel; Yağcı, Lara; Arapi, Berk; Albrahimi, Ergida; Balkanay, Ozan Onur; Göksedef, Deniz; Ömeroğlu, Suat Nail (Cerrahpaşa Medical Journal, 2025)
Objective: This study aims to evaluate the outcomes of patients with popliteal artery aneurysms (PAAs) who underwent open posterior surgical repair, focusing on the efficacy and safety of this approach. Methods: This retrospective study includes 31 patients with radiologically confirmed PAAs who underwent open posterior surgical repair between 2007 and 2023. Patient demographics, comorbidities, aneurysm characteristics, surgical techniques, and postoperative outcomes were analyzed. Revascularization was per formed using either prosthetic grafts or autologous saphenous veins. Follow-up included clinical and radio logical evaluation of graft patency and limb salvage. Results: The majority of the patients were male, and common comorbidities included hyperlipidemia and hypertension. Bilateral aneurysms were observed in 29% of cases, and 25% had coexistent abdominal aor tic aneurysms. Surgical revascularization was achieved using either prosthetic grafts or autologous saphe nous veins. Early postoperative complications included 1 amputation and a 25% rate of reintervention via embolectomy. However, long-term patency and limb salvage were successfully maintained. The mean follow-up duration for patency was 112.35 months (median: 114.63 months; range: 3.37-200.00 months), while for survival, it was 108.22 months (median: 114.40 months; range: 3.37-200.00 months). Kaplan Meier analysis showed no statistically significant difference in survival or graft patency between graft types. Conclusion: The findings indicate that the posterior approach is a secure and efficient surgical method for PAA repair, demonstrating acceptable rates of complications and reinterventions. These results align with existing literature emphasizing the long-term durability of open surgical techniques, particularly when per formed in experienced centers. Cite this article as: Tel Üstünışık Ç, Yağcı L, Arapi B, et al. Surgical management of popliteal artery aneurysms via posterior approach: our institutional experience. Cerrahpaşa Med J 2025, 49, 0041, doi:10.5152/cjm.2025.25041.